Frequency–dependence of power and efficiency for resonant inductive coupling and magnetoelectric wireless power transfer systems. (1st October 2022) - Andersen, Erik; Roundy, Shad; Truong, Binh Duc
Abstract: The frequency dependence of the maximum output power and efficiency of two wireless power transfer systems (WPTSs), resonant inductive coupling (RIC) and magnetoelectric (ME), are investigated. We find that in the weak–coupling regime, the power optimization and efficiency maximization problems are equivalent and yield the same optimal load and frequency. These properties apply to both topologies under consideration. Despite the apparent difference in the energy conversion mechanisms, the two structures result in similar explicit forms of maximum power delivered to the load, and so does the optimum transfer efficiency. We discuss the essential role of a figure of merit for each configuration and show how they affect the overall performance. For a weakly–coupled inductive WPTS, both the maximum transferred power and efficiency are positively proportional to drive frequency squared. In the case of a ME–based architecture, the dependence of power and efficiency on frequency is the consequence of the transducer geometry optimization problem, subject to a volume constraint. Under a constant mechanical quality factor condition, both quantities are linearly proportional to the operating frequency. While the focus of this paper is RIC and ME mechanisms, some of the findings are also valid for relevant inductive energy harvesting or magneto–mechano–electric WPTSs.